2015
DOI: 10.4049/jimmunol.1402058
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Regulates CD8+ Memory T Cell Differentiation and Survival in Response to Weak, but Not Strong, TCR Signals

Abstract: In response to primary Ag contact, naive mouse CD8+ T cells undergo clonal expansion and differentiate into effector T cells. After pathogen clearance, most effector T cells die, and only a small number of memory T cell precursors (TMPs) survive to form a pool of long-lived memory T cells (TMs). Although high- and low-affinity CD8+ T cell clones are recruited into the primary response, the TM pool consists mainly of high-affinity clones. It remains unclear whether the more efficient expansion of high-affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The current findings are consistent with previously published reports showing that IFN‐γ is associated with CD8 + effector/memory contraction and enhanced specificity . Moreover, Sercan et al demonstrated the importance of IFN‐γ receptor signaling in CD11b + innate cells in the control of CD8 + effector proliferation .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current findings are consistent with previously published reports showing that IFN‐γ is associated with CD8 + effector/memory contraction and enhanced specificity . Moreover, Sercan et al demonstrated the importance of IFN‐γ receptor signaling in CD11b + innate cells in the control of CD8 + effector proliferation .…”
Section: Discussionsupporting
confidence: 93%
“…IFN‐γ and provides indirect evidence that IFN‐γ may contribute to the observed decrease in CD8 + effector/memory cells. Furthermore, IFN‐γ signaling blocked the formation of memory precursor CD8 + T‐cells that responded to weak TCR agonists and instead promoted the accrual of high‐affinity memory CD8 + T‐cells . Although the F protein is highly antigenic, it does not contain the primary, immunodominant epitope, thus future studies will determine the effect of i.n.…”
Section: Discussionmentioning
confidence: 99%
“…). The mTOR pathway is well‐documented to promote the continuous production of IFN‐ γ by memory T cells and this cytokine regulates differentiation and survival in response to weak T‐cell receptor signals of memory T CD8 + cells . Blocking this pathway with mTORi should impair IFN‐ γ production, although the intracellular levels of IFN‐ γ in Tn, Tcm and Tem cells were not affected after including any mTORi in the culture (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The differentiation, proliferation and apoptosis of these varying T cell populations are controlled by a complex interplay of cytokines and interactions between the TCR and the peptide-HLA complex. While this process is not fully understood, cells with high affinity TCRs seem to be the most effective at lysing target cells and are most likely to become memory T cells 11,14. Thus, the ability to induce these high TCR affinity T cells specific for the target TAA is key to the success of peptide vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability to induce these high TCR affinity T cells specific for the target TAA is key to the success of peptide vaccines. High levels of IFN-γ have been linked to a weaker TCR signal caused by low affinity of the TCR to the HLA-peptide complex and this weak TCR signal has been shown to lead to early contraction of effector CTL populations 14,15. Similarly, while IL-2 is needed for CTL proliferation, high levels have been linked to production of regulatory T cells that may hinder effective clearance of targeted cancer cells.…”
Section: Discussionmentioning
confidence: 99%